Expression of BMP-2 in Vascular Endothelial Cells of Recipient May Predict Delayed Graft Function After Renal Transplantation - Nikolina Basic-Jukic; Marijana Gulin; Tvrtko Hudolin; Zeljko Kastelan; Lea Katalinic; Marijana Coric; Marija Varnai Veda; Vanja Ivkovic; Petar Kes; Bojan Jelakovic (Karger Publishers, 2016)
Background/Aims: Delayed graft function (DGF) is associated with adverse outcomes after renal transplantation. Bone morphogenetic protein-2 (BMP-2) is involved in both endothelial function and immunological events. We compared expression of BMP-2 in epigastric artery of renal transplant recipients with immediate graft function (IGF) and DGF. Methods: 79 patients were included in this prospective study. Patients were divided in IGF group (64 patients) and DGF group (15 patients). BMP-2 expression in intima media (BMP2m) and endothelium (BMP2e) of epigastric artery was assessed by immunohistochemistry. Results: Lower intensity of BMP2e staining was recorded in DGF compared to IGF. In DGF patients, 93% had no expression of BMP2e and 7% had 1st grade expression, compared to 45% and 41% in IGF group, respectively (P=0.001) (Pst grade expression). Patients who had BMP2e staining positive had lower odds for DGF (OR 0.059 [0.007, 0.477]) and this remained significant even after adjustment for donor and recipient variables, cold ischemia time, and immunological matching (OR 0.038 [0.003, 0.492]). Conclusions: Our results demonstrate that BMP-2 expression in endothelial cells of epigastric arteries may predict development of DGF.